Hematological phenotypes in GATA2 deficiency syndrome arise from aging, maladaptation to proliferation, and somatic events - Juncal Fernandez-Orth; Cansu Koyunlar; Julia M. Weiss; Emanuele Gioacchino; Hans de Looper; Geoffroy Andrieux; Mariëtte ter Borg; Joke Zink; Irene Gonzalez-Menendez; Remco Hoogenboezem; Baris Yigit; Kirsten J. Gussinklo; et al. (Blood Advances)
Abstract: The GATA2 transcription factor is a pivotal regulator of hematopoiesis. Disruptions in the GATA2 gene drive severe hematologic abnormalities and are associated with an increased risk of myelodysplastic syndromes and acute myeloid leukemia; however, the mechanisms underlying the pathophysiology of GATA2 deficiency still remain unclear. We developed 2 different mouse models that are based on serial and limiting donor-cell transplantation of (14-15 months) GATA2 haploinsufficient cells and mirror the symptoms of GATA2 deficiency. Similar to what has been observed in patients, our models showed that GATA2 haploinsufficiency leads to B lymphopenia, monocytopenia, lethal bone marrow failure (BMF), myelodysplasia, and lymphoblastic leukemia. Leukemia arises exclusively because of BMF, driven by somatic aberrations and accompanied by increased Myc target expression and genomic instability. These findings were confirmed in human GATA2+/− K562 cell lines showing defects in cytokinesis and are in line with the fact that monosomy 7 and trisomy 8 are frequent events in patients with myelodysplastic syndrome.